Karakteristik Pasien Penyakit Jantung Bawaan Dewasa Pirau Kiri ke Kanan dan Hipertensi Paru di RSUD Saiful Anwar Malang - Rahmawati, Novi; Yogibuana, Valerinna; Gultom, Yosafat; Triatmojo, Nicodemus (Jurnal Klinik dan Riset Kesehatan, 2024)
Background: The worldwide incidence of congenital heart disease (CHD) is estimated at 1.2 million cases out of 135 million live births each year. Pulmonaryarterial hypertension (PAH) is a frequent complication of congenital heart disease (CHD), especially in patients with left-to-right shunt. Adult CHD (ACHD) and ACHD- PAH patients present to health facilities in late phase conditions, because the early- stage symptoms are very uncommon, as a result the treatmentbecomes more difficult with a poor prognosis. Until now, there’s no national registry of ACHD and ACHD- PAH in Indonesia. Aim: Describe the demographic characteristics, clinical presentation, supporting examination findings, management, complications, and outcomes of ACHD and ACHD-PAH populations in Malang. Methods: Left to Right Shunt and Pulmonary Hypertention Registry is an observational study of adult patients (aged ≥ 18 years) diagnosed with left to rightshunt CHD and PAH at Saiful Anwar Hospital Malang. This study evaluated patients from November 2022 - October 2023 consecutively. Patients underwent a series of examinations including clinical examination, ECG, chest X-ray, SMWT, laboratory examination, transthoracic echocardiography and right heart catheterization. Results: Total sample of this registry is 124 samples. The majority of sample is young adult woman and ASD is the most common ACHD defect. The majority of sample (83.0%) is with symptoms with NT pro BNP median is 548 (152.1 – 2550.5). The majority of sample was WHO functional class II Conclusion: LET SHINE Registry is the first ACHD and ACHD-PAH in East Java Province which depict demographic, clinical presentation, hemodynamicpresentation pf ACHD and ACHD-PAH patient.